The research of nitriding process parameters influence applied on a high speed steel - Kakaš, Damir; Lupuljev, Dragiša (Journal of Production Engineering, 1986)
In this paper it was analysed the ion nitriding technology applied on high speed steel 0.7680. The most significant parameters of process were waried in the determined region according to metodology of experimental design. The results have been analysed by compUter. Conclusions about possibilities how to influence on ion nitriding results by changing the parameters of process have been given.